Using laxatives and/or enemas to accelerate the diagnosis in children presenting with acute abdominal pain: a randomised controlled trial study protocol - Marjolijn E W Timmerman; Monika Trzpis; Paul M A Broens (BMJ Publishing Group, 2018)
Introduction Many children with acute abdominal pain and suspicion of appendicitis are diagnosed with constipation. Nevertheless, it can be difficult to differentiate between acute constipation and acute appendicitis because of similar symptoms and lack of diagnostic criteria. Consequently, constipation is often missed despite repeated consultations at the emergency department. We hypothesise that the diagnostic process can be improved and adequate treatment accelerated by supporting faecal evacuation in children with acute abdominal pain.Methods and analysis An unblinded randomised controlled trial including children aged between 5 years and 18 years with acute abdominal pain and suspicion of acute appendicitis. Children who do not have a definitive diagnosis after the first consultation and who need to return for a second consultation will be randomised. The intervention group will receive laxatives and enemas, while the control group will receive no medication. If, after the second consultation, still no diagnosis is established, and a third consultation is needed, then the intervention group will receive only laxatives, and the control group will again not receive medication. The primary outcome will be the differences in abdominal pain scores obtained with FACES Pain Rating Scale and the visual analogue scale at first, second and possibly third consultation. The secondary outcome will be the number of consultations needed to reach final diagnosis.Ethics and dissemination Laxatives and enemas have proven to be safe and effective treatments for constipation in children. Adverse events are therefore not expected, however, should they occur, then the child concerned shall be properly followed and treated until the event is over. The local Medical Research Ethics Committee approved of this study and waived the otherwise mandatory insurance for human test subjects.Trial registration numbers Pre-results: CCMO NL44710.042.12 andEudraCT 2013-000498-56.